Vocabulary learning strategies between learners of Arabic major and non Arabic major at Malaysian public university - Sahid, Mohamad Khaidir; Mamat, Arifin; Mohamad Adnan, Mohamad Azrein (Internet Academy, 2020)
Vocabulary is acknowledged to be central to language learning. Vocabulary learning is important in acquiring a language learning. This study aims at investigating the vocabulary learning strategies used by Arabic and non-Arabic majors at a Public University in Malaysia. A sample of 282 students from both groups answered the Vocabulary Learning Questionnaire. The questionnaire is a combined self-developed and adapted version from the categories of VLS compiled by Schmitt. The study found that both groups agreed they believed words’ meanings are learned through multiple exposure of the words in different contexts through incidental learning. Significant differences were further identified in the beliefs concerning vocabulary learning. Most of AML responses showed more positive agreements on the beliefs than NAML, hence suggesting that learners with a background on the foreign language they are learning show more positive attitude towards the language compared to learners without any background in the language.